2012
DOI: 10.12693/aphyspola.122.485
|View full text |Cite
|
Sign up to set email alerts
|

Creep Behavior of a Zirconium Alloy Processed by Equal-Channel Angular Pressing

Abstract: A Zr2.5 wt%Nb alloy was processed by equal-channel angular pressing and then tested under creep conditions at 623 K using a tensile stress within the range from 120 to 300 MPa. The results show conventional power-law creep with a stress exponent of n > 3 which is consistent with an intragranular dislocation process involving the glide and climb of dislocations. It is demonstrated that diusion creep is not important in these tests. For comparison purposes, the experiments were conducted using both the unprocess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 22 publications
0
4
0
2
Order By: Relevance
“…In our previous works [12][13][14][15][16][17], it was found that the sample after 1 ECAP pass exhibited the highest creep resistance. This suggests that the highest creep resistance can be achieved in inhomogeneous ECAP-processed microstructure containing a high density of LAGBs but a lower density of HAGBs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous works [12][13][14][15][16][17], it was found that the sample after 1 ECAP pass exhibited the highest creep resistance. This suggests that the highest creep resistance can be achieved in inhomogeneous ECAP-processed microstructure containing a high density of LAGBs but a lower density of HAGBs.…”
Section: Discussionmentioning
confidence: 99%
“…Creep in polycrystalline materials after SPD processing was investigated on pure metals [10][11][12][13][14][15][16], alloys [17][18][19][20], and Cu-Al 2 O 3 composite [21]. However, there are a few reports documenting the creep properties and creep mechanisms of the ultrafine-grained (UFG) materials processed by different numbers of ECAP passes.…”
Section: Introductionmentioning
confidence: 99%
“…The microstructure analysis was conducted with BF TEM image and SAD diffraction. Sklenicka (2012) [17] studied the microstructure of Zr-2.5Nb with EBSD, and they commented that the grain sizes were not fully investigated due to the limited resolution in the characterization of the very small grains by the EBSD method. An investigation of the formation of ZrO in the zirconium structure by TKD and TEM showed that they are complementary techniques [18].…”
Section: Light Microscopymentioning
confidence: 99%
“…1). Однако, как показал анализ данных настоящей работы и литературных дан-ных, степень повышения σ B , σ S , H v может значительно отличаться от полученной для долговечности (известны случаи, когда τ после перевода образца в микрокристал-лическое состояние даже уменьшается) [10,[12][13][14][15][16][17].…”
Section: экспериментальные данные и их обсуждениеunclassified